Effects of various straw incorporation methods on the physicochemical properties and nutrient leaching of red soil - CHEN Yuni; SHENG Feng (Guan'gai paishui xuebao)
【Objective】Red soil in Southern China is typically deficient in structure and nutrients. Amending it with straw has been proposed as a method to improve its structure and fertility. This study experimentally examines the effects of different straw incorporation methods on the physicochemical properties of red soil, as well as nutrient leaching.【Method】The experiment was conducted using columns, where soils were repacked into columns and amended with crushed straw, straw powder, or straw ash. The control was soil without amendment. The columns were then subjected to leaching. At the end of the experiment, the physicochemical properties of the soil in each column were measured.【Result】Regardless of the type of straw, amending the soil with it reduced bulk density, increased total porosity and capillary porosity, enhanced soil organic matter, and increased most nutrients, while reducing nutrient leaching. Amending soil with crushed straw was most effective in increasing capillary porosity and reducing nitrate (NO- 3-N) leaching, as well as minimizing the losses of ammonium (NH+ 4-N) and total nitrogen (N). In contrast, amending the soil with straw powder was most effective in increasing soil ammonia nitrogen and available potassium content, while reducing the losses of total nitrogen and total phosphorus, and improving the stability of soil aggregates. Amending the soil with straw ash was most effective in increasing total soil porosity, soil organic matter, available phosphorus, and reducing total losses of nitrate (NO- 3-N), total phosphorus (P), and ammonium (NH+ 4-N). However, producing straw ash is environmentally unfriendly.【Conclusion】Among the three types of straw, amending soil with straw powder was the most effective in improving soil structure and the physicochemical properties of red soil. This method can be used as an improved agronomic technology to enhance the productivity of red soils.